Pengaruh Kepemimpinan Kepala Sekolah, Kompetensi Guru dan Komitmen Organisasi terhadap Implementasi Manajemen Terpadu di SDIT Yasir Cipondoh Kota Tangerang - Nusantara, Fajar Adipura (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to determine the influence of principal leadership, teacher competence and organizational commitment on the implementation of integrated management at SDIT Yasir Cipondoh, Tangerang City. This research is a quantitative study and the method used in this study is a survey research method. The sample of this study used a saturated sampling technique which used the entire population, namely all SDIT teachers at the Ibnu Rusydi Foundation Cipondoh, Tangerang City, totaling 50 people. The data collection techniques used were observation and questionnaires. The data analysis technique used was starting from the classical assumption test, multiple linear regression analysis, partial test (t-test) and Joint Test (F-test). The analysis was carried out to determine whether or not there was an influence of the three independent variables on the dependent variable. The results of the data analysis showed that principal leadership, teacher competence, and organizational commitment had a positive influence in improving the implementation of integrated management at SDIT Yasir Cipondoh.